A Searchable Laboratory-Acquired Infection Database. (December 2016) - Gillum, David; Krishnan, Partha; Byers, Karen
Published peer-reviewed accounts of laboratory-acquired infections (LAIs) are difficult to track and assess due to several underlying factors. Reports of LAI in peer-reviewed journals are recognized as "goal posts" for biosafety programs and may contain invaluable information for proactive steps to take to prevent a potential incident in the laboratory. Objectively reviewing published studies enhances prevention efforts and reinforces training by providing examples of LAI and associated procedures. In an effort to make this information more accessible, ABSA International has developed an online searchable database of peer-reviewed published LAIs. This article presents the questions included in the repository and discusses the need for consistency in the data being collected for LAIs. In addition, this article presents historical information leading up to the development of these questions, as well as the formalization of the online database of published LAIs.